Sensitivity and Specificity of Ultrasonography for Assessing Axillary Lymph Nodes in Breast Cancer Patients in Surakarta, Indonesia - Bellynda, Monica; Yarso, Kristanto Yuli; Rosati, Ari; Kamil, Muhammad Rizki; Muhammad, Faizal (Indonesian Journal of Cancer, 2025)
Background: Breast cancer is the most common malignancy in women worldwide. Early detection is effective in reducing breast cancer mortality by 25–30%. Staging assessment with sentinel lymph node biopsy (SLNB) is the gold standard for patients with clinically negative axillae. Ultrasound examination of the axillae is often performed as a preoperative treatment for breast cancer patients to determine the stage of the cancer, where regional axillary lymph node assessment can be related to the prognostic factors of breast cancer, as well as assessing the prognosis for distant metastases. This study aims to evaluate the sensitivity of ultrasound examination of the axillary lymph nodes in breast cancer.Method: This study employs a descriptive research method with a retrospective approach, utilizing secondary data and comprising 283 samples. Inclusion criteria included patients diagnosed with cervical carcinoma confirmed by histopathological evaluation and complete medical records documenting age, primary complaints, histopathological classification, and TNM staging. Data were processed and presented using descriptive statistics. The study was conducted at the Surakarta Hospital between 2020 and 2022. Inclusion criteria were breast cancer patients with stage T1-2 N0 M0 confirmed by histopathological examination who underwent axillary lymph node ultrasound examination in Surakarta. Data was taken from the medical records. Patient's initial, age, date of examination, clinical diagnosis, expertise of the ultrasound, and histopathology of the axillary lymph node were recorded. The gold standard is SLNB. The calculation of diagnostic validity was carried out using a 2x2 table, and then the sensitivity, specificity, positive predictive value, negative predictive value, and diagnostic accuracy of ultrasound were calculated.Results: 176 cases met the inclusion criteria, with 59.10% patients aged over 50 years old. Seventeen cases had positive ultrasound but negative histopathology examinations. Meanwhile, the remaining 15 cases had negative ultrasound but positive histopathology examinations. The sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and diagnostic accuracy results are as follows: 82%, 83%, 80%, 83%, 4.89, 0.21, and 82%, respectively.Conclusion: Ultrasound examination for assessing axillary lymph nodes is easy, inexpensive, effective, and safe. The results can be increased with better radiological methods and experience from higher-level operators.